Wholesale Issues for The Development of Wholesale Trade in Uzbekistan - Kholmamatov Diyor Haqberdievich (Genius Journals, 2022)
At the current stage of radical reforms in the economy of Uzbekistan, the role and importance of wholesale trade is growing. This is due to the fact that as a result of diversification of industrial production, the volume of production is increasing. Not only in industry, but also in agriculture, the volume of production is growing sharply. This makes it important to distribute products on time. This article discusses some topical issues of wholesale trade development in Uzbekistan
Keywords: Wholesale trade; wholesale market; domestic trade; foreign trade